2016
DOI: 10.12973/eurasia.2016.1527a
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating Creativity Gamification Rehabilitation System: The Application of PCA-ANFIS Based Emotions Model

Abstract: This study aims to explore the factors in a patient's rehabilitation achievement after a total knee replacement (TKR) patient exercises, using a PCA-ANFIS emotion modelbased game rehabilitation system, which combines virtual reality (VR) and motion capture technology. The researchers combine a principal component analysis (PCA) and an adaptive network-based fuzzy inference system (ANFIS) to present a predicting, artificial emotion model with a Plutchik emotional wheel in a 3D Gesture gamification rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“… Boot and colleagues (2016) reported that the participants in their study had a low proficiency with mobile technologies. Su and Cheng (2016) described that approximately half of their participants had experience with motion-capturing technology before the study. Furthermore, two of the reviewed studies ( Hiraoka et al, 2016 ; Sun et al, 2017 ) mentioned that participants in their study had no prior experience with the investigated technologies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Boot and colleagues (2016) reported that the participants in their study had a low proficiency with mobile technologies. Su and Cheng (2016) described that approximately half of their participants had experience with motion-capturing technology before the study. Furthermore, two of the reviewed studies ( Hiraoka et al, 2016 ; Sun et al, 2017 ) mentioned that participants in their study had no prior experience with the investigated technologies.…”
Section: Resultsmentioning
confidence: 99%
“… Li and colleagues (2016) studied the effects of playfulness in exergames on depression using Wii Fit Sports exergames and Wii Fit fitness exercises. Katajapuu and colleagues (2017) and Su and Cheng (2016) reported studies using Microsoft Kinect to capture the movements of the players that then controlled the exergame. Physical health was also targeted in the study by Steinert and colleagues (2018) ; however, their intervention more resembled the common gamified exercise solutions delivered via mobile devices, with the participants carrying an activity tracker and performing exercises provided by the mHealth solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, games and Virtual Reality (VR) have been developed as intervention tools in rehabilitation [13,14,15,3]. In the literature we can find studies that show that VR can increase motivation whilst used in rehabilitation and also allows realistically situations that otherwise would be difficult for patients [16].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the Kinect upper limb exercise rehabilitation interaction technology is applied to the robot-assisted exercise rehabilitation training, and the Kinect-based somatosensory interaction is carried out. The robot assisted rehabilitation training method and system research will further improve and improve the technical level of human-machine cooperative rehabilitation training, which has important academic significance and clinical application value [13]- [15]. However, due to the imperfect limb movement function of the patient, it is impossible to carry out rehabilitation training independently.…”
Section: Introductionmentioning
confidence: 99%